Synet. Et ungdomsdigt af Grundtvig - Grundtvig, N. F. S. (Grundtvig-studier, 1989)
The Vision By Grundtvig. So far this early poem by Grundtvig has only been printed in an appendix to ’’ Christian Molbech and Nikolai Frederik Severin Grundtvig. A Correspondence’’, edited by L. Schr.der, Copenhagen 1888. A personal letter to the historian Chr. Molbech, who was a friend of Grundtvig in his youth, is attached and is found with 5 other poems from 1805 to 1807 in the Royal Library (New Royal Collection 3091 4.) in Copenhagen.